Greening of Capitalism: How Asia Is Driving the Next Great Transformation - Mathews, John (Stanford University Press, 2014)
As China, India, and other industrializing giants grow, they are confronted with an inconvenient truth: They cannot rely on the conventions of capitalism as we know them today. Western industrialism has achieved miracles, promoting unprecedented levels of prosperity and raising hundreds of millions out of poverty. Yet, if allowed to proceed unencumbered, this paradigm will do irreversible harm to the planet. By necessity, a new approach to environmentally conscious development is already emerging in the East, with China leading the way. Positioning its argument against zero-growth advocates and free-market environmentalists, Greening of Capitalism charts this transformation and sketches out a framework for more sustainable capitalism. State-mandated changes in energy use (as opposed to carbon taxes), a circular flow of resources (as opposed to emissions standards), and the introduction of new financial instruments that support green growth are cornerstones of China's framework. John A. Mathews argues that these tenets will be emulated around the worldfirst in India and Brazil. In light of this emerging shift, Mathews considers core debates over national security, international relations, and economic policy, ultimately addressing the question of whether these measures will be far-reaching or timely enough to prevent further damage.
Keywords: business & economics; economic policy; energy; government & business; industries; public policy; sustainable capitalism

Le religioni della politica: Fra democrazie e totalitarismi - Gentile, Emilio (Gius.Laterza & Figli Spa, 2014)
La sacralizzazione della politica accade ogni volta che un'entità politica – la nazione, la democrazia, lo Stato, la razza, la classe, il partito, il movimento – è trasformata in una entità sacra, in un oggetto di devozione e di culto, ed è collocata al centro di un sistema di credenze, di simboli e di riti. Nascono allora le religioni della politica, che non si identificano con un unico tipo di ideologia e di regime: esse possono sacralizzare la democrazia o l'autocrazia, l'eguaglianza o la disuguaglianza, la nazione o l'umanità.
Keywords: essence of fascism; fascism; history / modern / 21st Century; political philosophy

Karl Polanyi: New Perspectives on the Place of the Economy in Society - Harvey, Mark; Ramlogan, Ronnie; Randles, Sally (Oxford University Press, 2014)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology and social policy. Newly available in paperback, this volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations and European labour markets.
Keywords: business & economics; economic theory

Making Capitalism Fit For Society - Crouch, Colin (John Wiley & Sons, 2014)
Capitalism is the only complex system known to us that can provide an efficient and innovative economy, but the financial crisis has brought out the pernicious side of capitalism and shown that it remains dependent on the state to rescue it from its own deficiencies. Can capitalism be reshaped so that it is fit for society, or must we acquiesce to the neoliberal view that society will be at its best when markets are given free rein in all areas of life? The aim of this book is to show that the acceptance of capitalism and the market does not require us to accept the full neoliberal agenda of unrestrained markets, insecurity in our working lives, and neglect of the environment and of public services. In particular, it should not mean supporting the growing dominance of public life by corporate wealth. The world’s most successful mature economies are those that fully embrace both the discipline of the market and the need for protection against its negative outcomes. Indeed, a continuing, unresolved clash between these two forces is itself a major source of vitality and innovation for economy and society. But maintenance of that tension depends on the enduring strength of trade unions and other critical groups in civil society - a strength that is threatened by neoliberalism’s increasingly intolerant onward march. Outlining the principles for a renewed and more assertive social democracy, this timely and important book shows that real possibilities exist to create a better world than that which is being offered by the wealthy elites who dominate our public and private lives.
Keywords: business & economics; capitalism; economic theory

The Passage West: Philosophy After the Age of the Nation State - Marramao, Giacomo (Verso Books, 2014)
In this ambitious work, Giacomo Marramao proposes a radical reconceptualization of the world system in our era of declining state sovereignty. He argues that globalization cannot be reduced to mere economics or summarized by phrases such as ‘the end of history’ or the ‘westernization of the world’. Instead, we find ourselves embarking on a passage to a new, post-nation state age destined to transform all civilizations – and to disrupt Western geopolitical dominance. To confront the challenges of this interregnum one must think in terms of a new and radical universalism, a universalism of difference able to revitalize politics and to demythologize identity.Building on the great interwar discussion between Spengler, Junger, Schmitt and Heidegger, Marramao’s new work engages with Habermas, Derrida and post-colonialism. Arguing against the classic Western pretension to universal norms of democracy and reason, he develops instead the idea of a ‘universal politics of difference’. KM - contains chapter: Gift, exchange, obligation: Karl Polanyi and social philosophy
Keywords: exchange; international relations; religious philosophy; social philosophy

The Power of Market Fundamentalism - Block, Fred; Somers, Margaret R. (Harvard University Press, 2014)
What is it about free-market ideas that give them tenacious staying power in the face of such manifest failures as persistent unemployment, widening inequality, and the severe financial crises that have stressed Western economies over the past forty years? Fred Block and Margaret Somers extend the work of the great political economist Karl Polanyi to explain why these ideas have revived from disrepute in the wake of the Great Depression and World War II, to become the dominant economic ideology of our time.Polanyi contends that the free market championed by market liberals never actually existed. While markets are essential to enable individual choice, they cannot be self-regulating because they require ongoing state action. Furthermore, they cannot by themselves provide such necessities of social existence as education, health care, social and personal security, and the right to earn a livelihood. When these public goods are subjected to market principles, social life is threatened and major crises ensue.Despite these theoretical flaws, market principles are powerfully seductive because they promise to diminish the role of politics in civic and social life. Because politics entails coercion and unsatisfying compromises among groups with deep conflicts, the wish to narrow its scope is understandable. But like Marx's theory that communism will lead to a "withering away of the State," the ideology that free markets can replace government is just as utopian and dangerous.
Keywords: United States history; business & economics; economic history; economic policy; economic theory; free enterprise; political economy; political science; public policy; sociology

The Rise and Fall of Ireland's Celtic Tiger: Liberalism, Boom and Bust - Ó Riain, Seán (Cambridge University Press, 2014)
In 2008 Ireland experienced one of the most dramatic economic crises of any economy in the world. It remains at the heart of the international crisis, sitting uneasily between the US and European economies. Not long ago, however, Ireland was celebrated as an example of successful market-led globalisation and economic growth. How can we explain the Irish crisis? What does it tell us about the causes of the international crisis? How should we rethink our understanding of contemporary economies and the workings of economic liberalism based on the Irish experience? This book combines economic sociology and comparative political economy to analyse the causes, dynamics and implications of Ireland's economic 'boom to bust'. It examines the interplay between the financial system, European integration and Irish national politics to show how financial speculation overwhelmed the economic and social development of the 1990s 'Celtic Tiger'.
Keywords: business & economics; economic conditions; economic development; economic history; economic policy; liberalism; political science; public policy

The Global Development Crisis - Selwyn, Benjamin (John Wiley & Sons, 2014)
The central paradox of the contemporary world is the simultaneous presence of wealth on an unprecedented scale, and mass poverty. Liberal theory explains the relationship between capitalism and poverty as one based around the dichotomy of inclusion (into capitalism) vs exclusion (from capitalism). Within this discourse, the global capitalist system is portrayed as a sphere of economic dynamism and as a source of developmental opportunities for less developed countries and their populations. Development policy should, therefore, seek to integrate the poor into the global capitalist system. The Global Development Crisis challenges this way of thinking. Through an interrogation of some of the most important political economists of the last two centuries Friedrich List, Karl Marx, Leon Trotsky, Joseph Schumpeter, Alexander Gerschenkron, Karl Polanyi and Amarta Sen, Selwyn argues that class relations are the central cause of poverty and inequality, within and between countries. In contrast to much development thinking, which portrays ‘the poor’ as reliant upon benign assistance, this book advocates the concept of labour-centred development. Here ‘the poor’ are the global labouring classes, and their own collective actions and struggles constitute the basis of an alternative form of non-elitist, bottom-up human development.
Keywords: business & economics / development; economic development; embedded markets; political science / public policy / general; socialism

The Legacy of Karl Polanyi: Market, State and Society at the End of the Twentieth Century - Mendell, Marguerite; Salée, Daniel (Palgrave Macmillan UK, 2014)
The Great Transformation by Karl Polanyi, written in 1944, is a twentieth-century classic. It presents a passionate critique of the inhumanity of liberal capitalism, an inhumanity which, Polanyi thought, could never be repeated. The social and political institutions developed in the post-War period not only protected society from the cruelty of the self-regulating market, but were essential to enable the market itself to function. The history of the market, Polanyi tells us, is a history of regulation.
Keywords: Great Transformation, The (Book); business & economics; economic theory; regulation